Rekonstrusi Asas Legalitas Materil Dalam Pemidanaan Di Masyarakat Hukum Adat Kampung Kuta Kabupaten Ciamis - Gios Adhyaksa; Sarip Hidayat; Erga Yuhandra (JURNAL HUKUM PELITA, 2025)
Enforcement principle legality formal in in the Criminal Code​ Wetboek Van Strafrecht Voor Nederlanshe Indie (WvS -NI) in Indonesia has significant weakness.​ Weakness main from principle This is limit its vastness criminalization to act criminal law. Number 1 of 2023 concerning the Criminal Code​ change principle legality from principle legality formal become principle legality material, principle legality material determine that base worthy convicted a action is living law​ in society (law) No written). Implementation principle This in a way substantial expand range principle legality and in philosophical give respect to custom customs that still exist is in Indonesia at the moment This. The approach method used in study This that is juridical - empirical, researcher face to face direct with society Kuta Village Customary Law Community as object research. Results and Discussion Reform of Indonesian Criminal Law by Law Number 1 of 2023 concerning the Criminal Code​ in a way firm show that expansion of the Law no written that has been there is in Indonesia applied Because provision said , the Kuta Village community has law customs that are not written known​ as " taboo ", which is tradition inheritance local which is guarded and obeyed by the people of Kuta Village. If there is violation, violation will completed through institution customs and individuals who violate will given sanctions custom